A Systemic Framework to facilitate large and complex IT transformational Programs. (28th October 2015) - Kummamuru, Supriya; Hussaini, Syed W
Abstract: This paper presents a systemic framework for addressing the distinct challenges of Program management in the Information Technology (IT) services Industry environment. It was an outcome of the work carried out internally in the organization. The study involved identifying the challenges and defining the framework using a multi modeling approach. It was found Programs were treated with the same lens as projects, thereby missing the big picture and the benefits synthesized in a Program. Programs are a collection of projects, they differ in terms of scope, size, scale & complexity with respect to people involved, requirements, interfaces, time required etc. while programs are large and deliver benefits, projects deliver outcomes. The study also reviewed the existing program management frameworks and models for addressing these challenges and found they were domain agnostic and some areas specific to IT domain were not addressed. The nature of every IT programs is distinct because it belongs to different client domains, technology changes are rapid, and requirements keep changing as a result of changes in the environmental. The study identified several challenges which were then organized under five dimensions, each having similar concerns. Solutions were defined under each of these dimensions, they included new systemic frameworks and positioning existing ones appropriately. Given the enormity of the context not all areas could be addressed, which will be taken up latter. Some of the suggested models have also been validated in client program's contexts. This paper covers the multi modeling methodology used for the study, the findings and the proposed framework for Program Management at a conceptual level, because the solutions are proprietary and are the Intellectual Property (IP) of the organization.